The Role of Robotics-Driven Productivity, Profit, and Employee Satisfaction in Enhancing Sustainability in the Beverage Industry - Jimoh Adams Lukman; Zi Jian Oh; Muhammad Azim Akmal bin Johani; Muhammad Alimi bin Mohd Tarmizi; Muhammad Afiq Hakimie bin Ahmad Sobri; Muhammad Amar Basyir bin Sulaiman; Suryo Wirawan; Dhymas Pramana Wicaksana; Mikita Trusevich; Daisy Mui Hung Kee (Asia Pacific Journal of Management and Education (APJME), 2024)
This research examines the perceptions of individuals from diverse backgrounds regarding the role of robotics in the Coca-Cola industry, focusing on productivity, profitability, and employee satisfaction. The objective was to evaluate how robotics impacts organizational efficiency and sustainability in beverage manufacturing, especially Coca-Cola. A quantitative methodology was employed, utilizing a Google Form questionnaire distributed to 50 respondents from Malaysia, Indonesia, India, and Belarus. The survey assessed the perceived productivity, profitability, and satisfaction related to robotic integration in Coca-Cola's operations. Results indicated that respondents rated the productivity of robotics positively, with a mean score of 3.84, suggesting a strong perception of automation’s efficiency. Profitability was similarly viewed favorably, with a mean of 3.86, indicating that robotics contributes to organizational profitability. Employee satisfaction with robotics had a slightly lower mean score of 3.82, reflecting a neutral to positive outlook. In conclusion, robotics significantly enhances productivity and profitability in the beverage industry, while employee satisfaction, though important, has a secondary impact on sustainability outcomes.